Don't Underestimate the Benefits of Being Misunderstood. (June 2017) - Gibson, Edward; Tan, Caitlin; Futrell, Richard; Mahowald, Kyle; Konieczny, Lars; Hemforth, Barbara; Fedorenko, Evelina
Being a nonnative speaker of a language poses challenges. Individuals often feel embarrassed by the errors they make when talking in their second language. However, here we report an advantage of being a nonnative speaker: Native speakers give foreign-accented speakers the benefit of the doubt when interpreting their utterances; as a result, apparently implausible utterances are more likely to be interpreted in a plausible way when delivered in a foreign than in a native accent. Across three replicated experiments, we demonstrated that native English speakers are more likely to interpret implausible utterances, such as "the mother gave the candle the daughter, " as similar plausible utterances ("the mother gave the candle to the daughter") when the speaker has a foreign accent. This result follows from the general model of language interpretation in a noisy channel, under the hypothesis that listeners assume a higher error rate in foreign-accented than in nonaccented speech.